ENHANCING STUDENTS’VOCABULARY EXPERTISE THROUGH LYRICS OF SONGS - Priskilla Rantung; Nhita V.F. Liando; Jenie Posumah (KOMPETENSI, 2022)
The aim of this research is to find out what extent song lyrics can be used to improve students‟ vocabulary mastery. The subjects of this research were the seventh grade students of SMP Berea Tondano. The seventh grade students in SMP Berea Tondano Class consisted 20 students. This research used a quantitative research. The instrument of this research was tests pre-test and post- test. The result of data analysis indicated that the mean score of the post-test was higher than the mean score of the pre-test. It concludes that the results of the post- test increased significantly. These results indicate that song lyrics are an effective media to used. It suggests that English teachers to try using song lyrics as a media in the teaching learning vocabulary as it more enjoyable and and stressfree.